Ethical Patterns of Communication in the Framework of the Quran Islamic Perspective - Dedi Masri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study examines the Ethical Pattern of Communicating in the Framework of the Qur'an from an Islamic Perspective. The focus of this research is to find out what the patterns and ethics are when communicating according to the Qur'an and Islam. The formulation of the problem in this study is 1. What is the meaning of communication in the Qur'an from an Islamic Perspective? 2. What are the Communication Ethics in the Qur'an and Islam, 3. What are the Communication Principles in Islam and the Qur'an?. The research methodology used in this scientific paper uses the library method by taking from various sources relevant to the discussion in this study, both from previous journals and several supporting books. The results of this study are that there are several principles in communicating according to the Qur'an, namely Qaulan Sadida, Qaulan Baligha, Qaulan, Ma'rufa, Qaulan Karima, Qaulan Layina, Qaulan Maysura, then the results of further research Communication has ethics in its delivery and prayer as a means in communicating with God. The pattern of Communicating Ethics in the Qur'an aims to create a vertical relationship with Allah SWT and also with fellow human beings.